Challenges faced by school heads in the administration of inclusive education in primary schools in the Southern Stars Cluster of Bulawayo Central District - Malaba, Kudzani (Midlands State University, 2019)
The researcher was motivated by the way school heads administered inclusive education in primary schools. As a specialist teacher, the researcher had noted with concern how school heads administered inclusive education in various schools she had taught in. This compelled the researcher to come up with the topic: “Challenges faced by school heads in the administration of inclusive education in primary schools in the Southern Stars Cluster of Bulawayo Central District”. The study sought to find causes/reasons and solutions as to why inclusive education was a challenge to the heads to administer. The researcher reviewed related literature, gathered data from 5 school heads, 5 deputy school heads and a schools’ inspector. The data was presented, analysed and discussed. The study established that most of the school heads and their deputies did not have adequate professional qualifications in special needs education. Lack of adequate learning and teaching, human and financial resources impacted negatively on the administration of inclusive education. Challenges also included unfriendly infrastructure in schools, parental and teachers’ lack of knowledge and skills as major factors that hindered the administration of inclusive education. The above factors were fuelled by the government’s lack of commitment and follow up on policy implementation. It was therefore recommended that the government took the initiative in putting in place measures that would see schools introduce inclusive education at a regulated pace. School heads should also desist from running schools like their personal enterprises and be non-selective when enrolling learners. There should be involvement of parents, community and other stakeholders in the education sector for inclusive education to be fully administered.